Comparison of the Effect of Different Heat Treatment Processes on Microstructure and Mechanical Properties of Stainless Steel Clad Plate - Jin, H.R.; Yang, X.K.; Yi, Y.L. (Проблемы прочности, 2017)
To improve the mechanical properties and corrosion resistance of 304/Q345R stainless steel clad plate, different heat treatment processes (oil cooling, oil cooling and tempering, oil cooling to 450°C as well as air cooling) have been performed after hot rolling. The microstructure, mechanical properties and corrosion resistance have been analyzed after conducting air cooling and heat treatment. The precipitated phases near the cladding interface have been measured using the energy spectrum analysis. The results imply that after hot rolling and air cooling the base layer microstructure is composed of ferrite and pearlite layers, while the overall strength of the clad plate remains to be low. The corrosion resistance is shown to be insignificant due to the higher precipitation of Cr carbide on the stainless steel side. After oil cooling, the hard phases of martensite and bainite dominate in the base layer microstructure. The plate strength has been enhanced, but its plasticity is insufficient. After tempering, the ductility value is considerably improved, however, it still fails to satisfy the requirements. After being oil cooled to 450°‘C and air cooled, the microstructure is found to be mainly composed of bainite, ferrite, and a small amount ofpearlite. The clad plate mechanical properties, such as strength, plasticity as well as corrosion resistance, have been significantly enhanced.